The inventory of mollusc species and its potent on seagrass bed in Kei Kecil Islands, Southeast Moluccas - AGUS KUSNADI; TEDDY TRIANDIZA; UDHI EKO HERNAWAN (Society for Indonesian Biodiversity, 2008)
Inventory of mollusk species and its potential on sea grass bed in Kei Kecil islands, Southeast Moluccas have been conducted by using quadrate-transect line method. The study was carried out in February-August 2007. There were 103 species of mollusk observed, 80 species belong to gastropods and 23 belong to bivalves. From the total species, 72 of them were reported as the potential species and the others still unknown. Most of potential group was used as food resources (55 species) and other species were potential as decoration, souvenir, ornament, and accessories (31 species). Some species were potential for building material, knife tool, barter tool and bioactive compounds. The top shells (Trochus niloticus), the giant clams (Tridacna spp. and Hippopus hippopus) and the abalone (Haliotis spp.) were the major trading commodities for shellfish fisheries.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: inventory, mollusk, potency, Kei Kecil.